The structured hypergraph as a structural model for organized systems - Giles, Kinsley; Morales, Carlos (Rev. Téc. Fac. Ing. Univ. Zulia)
The current trend in computing is to introduce more formality into the field. These trends, which may be catalogued as physicalist, will probably introduce substantial progress in this field. This paper presents a structural model for organized systems with multithreaded hierarchies. The formalization introduced by the Theory of general systems is chosen as the starting point. The concept of organized system with multithreaded hierarchies is then unfolded using the structured hypergraph taking agents, affects and interactions as primitive elements. This formalization would lead o a better control and greater capacity for expression in the design process. Furthermore, as expected in every physicalist trend, there is a potential for increasing design capacity and widening the field of computing.